2011
DOI: 10.1152/ajpregu.00039.2011
|View full text |Cite
|
Sign up to set email alerts
|

Thermotolerance and heat acclimation may share a common mechanism in humans

Abstract: Thermotolerance and heat acclimation are key adaptation processes that have been hitherto viewed as separate phenomena. Here, we provide evidence that these processes may share a common basis, as both may potentially be governed by the heat shock response. We evaluated the effects of a heat shock response-inhibitor (quercetin; 2,000 mg/day) on established markers of thermotolerance [gastrointestinal barrier permeability, plasma TNF-α, IL-6, and IL-10 concentrations, and leukocyte heat shock protein 70 (HSP70) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
119
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(131 citation statements)
references
References 69 publications
12
119
0
Order By: Relevance
“…There may be shared pathways with the concept of cross-tolerance, where adaptations to one stressor confer protection via molecular, cellular and neural interactions to other forms of stressor (Horowitz 2014;Horowitz and Robinson 2007). This process is thought to be mediated, in part, by intra-cellular heat shock proteins (Hsp's), and it has been suggested that acquired thermotolerance (the accumulation of protective Hsp's within cells following heat exposure), and systemic adaptations to heat acclimation share a common pathway (Kuennen et al 2011). This may be pertinent since EIMD has been shown to increase Hsp72 and Hsp27 expression within muscle cells following EIMD (Paulsen et al 2009;Thompson et al 2001), and that the changes we observed during HS on EIMD trial 2, reflect similar adaptations to that observed during heat acclimation (reduced exercising Tre, earlier sweating onset, reduced thermal sensation).…”
Section: Discussionmentioning
confidence: 99%
“…There may be shared pathways with the concept of cross-tolerance, where adaptations to one stressor confer protection via molecular, cellular and neural interactions to other forms of stressor (Horowitz 2014;Horowitz and Robinson 2007). This process is thought to be mediated, in part, by intra-cellular heat shock proteins (Hsp's), and it has been suggested that acquired thermotolerance (the accumulation of protective Hsp's within cells following heat exposure), and systemic adaptations to heat acclimation share a common pathway (Kuennen et al 2011). This may be pertinent since EIMD has been shown to increase Hsp72 and Hsp27 expression within muscle cells following EIMD (Paulsen et al 2009;Thompson et al 2001), and that the changes we observed during HS on EIMD trial 2, reflect similar adaptations to that observed during heat acclimation (reduced exercising Tre, earlier sweating onset, reduced thermal sensation).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent human study by Kuennen et al, 36 the administration of 2,000 mg/day of quercetin, an HSP pathway inhibitor, prevented the thermal responses and the improved intestinal permeability seen during a program of heat acclimation. On the other hand, ingestion of glutamine which increases HSP70 synthesis, prevented endotoxin release and the inflammatory response seen in the same unacclimated subjects without glutamine supplementation during an acute exercise bout in the heat.…”
Section: 36mentioning
confidence: 99%
“…36 If the HSP pathway is a major trigger for heat acclimation adaptations, then a malfunction in this system should have serious consequences for heat tolerance. In a study by Moran et al, 33 soldiers who failed to upregulate HSP during heat acclimation had more severe heart rate and body temperature responses during a HTT and were therefore classified as heat intolerant.…”
Section: 36mentioning
confidence: 99%
“…Ryan et al showed that treadmill exercise results in no apparent increase in HSP70 protein expression in human leukocytes. 142 Similarly, 2 50-min bouts of moderate intensity aerobic exercise 143,144 do not affect HSP70 levels in peripheral blood mononuclear cells (PBMCs). In our recent studies, strenuous treadmill running (rectal temperature of 40 C) produces a timedependent increase in HSP70 protein expression in peripheral leukocytes, but the difference did not reach statistical significance.…”
Section: Exercise and Hsp70 Protein Expression In Animalsmentioning
confidence: 99%
“…[158][159][160][161][162][163][164][165][166] When examining exercise training effects on HSP70 protein expression in humans, it has been shown that a 7-d heat acclimation protocol consisting of 2 50-min exercise bouts in a warm environmental chamber elevates subjects' core temperature to 39 C and results in a significant increase in HSP70 protein expression in peripheral leukocytes at 4-h post-exercise. 144 Similarly, a 10-d acclimation program involving treadmill walking or running in a hot environment augments HSP70 content in peripheral blood mononuclear cells. 143,167,168 Elevation of HSP70 in response to high-intensity and long-term training is also found after an 11-d training program, but not in response to short or moderate intensity exercise.…”
Section: Exercise and Hsp70 Protein Expression In Animalsmentioning
confidence: 99%